Digital transformation and loyalty programs in the Portuguese retail sector - Vieira, Catarina Santos Palhares (2021)
There is an increasing globalisation, in the grocery retail market, where competition and Digital Transformation are constantly evolving. These aspects, along with the high costs of acquiring new clients, lead companies to implement loyalty programs. This tool is essential to create and maintain customer´s loyalty and, consequently, grow and retain market share. Nevertheless, there is limited information about retail companies transforming themselves digitally to retain clients. Thus, the aim of this thesis is to understand how, in this sector, a loyalty program can be successfully implemented within a digitalization scenario. Therefore, a framework is proposed, regarding the implementation process of an effective loyalty program, in a Digital Transformation context. Since the desired outcome and key contribution of this dissertation is the framework, and its approval, the principal methodology used is the Design Science Research, given that it creates instruments to answer real problems and to contribute with knowledge. Besides this research method, there are two other contributions to validate the framework, which are “company X” and “the grocery retail industry”, through interviews. In order to help analysing the participant´s answers, regarding the framework´s variables, the VOSviewer program is used. From this analysis, it is possible to validate the conceptual framework and the positive impact that Digital Transformation has on the processes and loyalty programs. This transformation allows companies to improve services and offer a better value proposition, leading to the loyalty of customers. The framework is a contribution to that goal.